Research Synthesis of La3+ Doped TiO2 Nanoparticles by Hydrothermal Method, Study on Photocatalytic Activity of Decomposition of Methylene Blue under Ultraviolet Irradiation - Thi Minh Hue, Do; Thi Tuyet Mai, Nguyen; Van Chau, Tran; Thi Thu Huyen, Tran; Thi Lan, Nguyen; Ngoc Dung, Ta; Dang Chinh, Huynh (VNU Journal of Science: Natural Sciences and Technology; Vol 35 No 3, 2019)
In this study, with the aim of improving the photocatalytic efficiency of TiO 2 , we studied the synthesis of La 3+ doped TiO 2 (with doped rates 1%, 2.5%, 5% mol/mol compared to Ti 4+ ) by hydrothermal method. The hydrothermal condition was set at 180 °C for 12 hours. Material characteristics were investigated by XRD, SEM and solid UV-Vis methods. The results show that, all prepared materials have a crystal particle size of about nano-meters, small and smooth (4.5¸6.5 nm). La 3+  doped TiO 2 samples had a shift towards longer wavelengths (l» 400¸500 nm) compared to non-doped TiO 2 sample (l£ 380 nm). The band gap energy (Eg) of La 3+ doped TiO 2 samples was reduced to 3.04¸3.10 eV . The yield of MB degradation of La 3+ doped TiO 2 at 5% mol/mol reached the highest ~93% after 60 minutes under ultraviolet irradiation. Keywords Anatase TiO 2 , photocatalysis, La 3+ doped TiO 2 , hydrothermal method, ultraviolet irradiation.   References [1] D. Nassoko, Y. F. Li, H. Wang, J. L. Li, Y. Z. Li, Y. Yu, Nitrogen-doped TiO2 nanoparticles by using EDTA as nitrogen source and soft template: Simple preparation, mesoporous structure, and photocatalytic activity under visible light, Journal of Alloys and Compounds. 540 (2012) 228-235. https://doi.org/10.1016/j.jallcom.2012.06.085. [2] M. Khatamian, S. Hashemian, A. Yavari, M. Saket, Preparation of metal ion (Fe3+ and Ni2+) doped TiO2 nanoparticles supported on ZSM-5 zeolite and investigation of its photocatalytic activity, Materials Science and Engineering B. 177 (2012) 1623-1627. http://dx.doi.org/10.1016/ j.mseb.2012.08.015. [3] X. Zhang, Q. Liu, Visible-light-induced degradation of formaldehyde over titania photocatalyst co-doped with nitrogen and nickel, Applied surface Science. 254(15) (2008) 4780-4785. https://doi.org/10.1016/j.apsusc.2008.01.094. [4] Y. Wang, H. Cheng, L. Zhang, Y. Hao, J. Ma, B. Xu, W. Li, The preparation, characterization, photoelectrochemical and photocatalytic properties of lanthanide metal-ion-doped TiO2 nanoparticles, Journal of Molecular Catalysis A: Chemical. 151 (2000) 205-216. https://doi.org/10. 1016/s 1381-1169(99)00245-9 [5] M. Meksi, G. Berhault, C. Guillard, H. Kochkar, Design of TiO2 nanorods and nanotubes doped with lanthanum and comparative kinetic study in the photodegradation of formic acid, Catalysis Communications. 61 (2015) 107-111. https://doi. org/ 10.1016/j.catcom.2014.12.020. [6] Q. Wang, S. Xu, F. Shen, Preparation and characterization of TiO2 photocatalysts co-doped with iron (III) and lanthanum for the degradation of organic pollutants, Applied Surface Science. 257 (2011) 7671-7677. https://doi.org/10.1016/j. apsusc.2011.03.157. [7] L. Elsellami, H. Lachheb, A. Houas, Synthesis, characterization and photocatalytic activity of Li, Cd-, and La-doped TiO2, Materials Science in Semiconductor Processing. 36 (2015) 103-114. https://doi.org/10.1016/j.mssp.2015.03.032. [8] J. Nie, Y. Mo, B. Zheng, H. Yuan, D. Xiao, Electrochemical fabrication of lanthanum-doped TiO2 nanotube array electrode and investigation of its photoelectrochemical capability, Electrochimica Acta. 90 (2013) 589-596. http://dx.doi.org/10. 1016/j.electacta. 2012.12.049. [9] Y. Chen, Q. Wu, C. Zhou, Q. Jin, Enhanced photocatalytic activity of La and N co-doped TiO2/diatomite composite, Powder Technology. 322 (2017) 296-300. http://dx.doi.org/10.1016/ j.powtec.2017.09.026. [10] I. Ganesh, P. P. Kumar, I. Annapoorna, J. M. Sumliner, M. Ramakrishna, N. Y. Hebalkar, G. Padmanabham, G. Sundararajan, Preparation and characterization of Cu-doped TiO2 materials for electrochemical, photoelectrochemical, and photocatalytic applications, Applied Surface Science, 293 (2014) 229-247. http://dx.doi.org/10. 1016/j.apsusc.2013.12.140.